Requirements Of Applying Marketing Quality Management In Commercial Banks (Field Study On Private Commercial Banks Working In Syria) - Ammar, Koussay; Halloum, Sinan; Mohammed, Bassam (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aimed to determine the availability of the requirements of applying the marketing quality management in private commercial banks operating in Syria, where the study community is among the workers in these banks. The study used the deductive approach as a general approach to research, descriptive approach, and the questionnaire as a tool to collect data from a soft sample, where (150) questionnaires were distributed and (135) questionnaires valid for analysis were retrieved. The study adopted the appropriate analysis methods using the spss statistical package such as Studenet test, Pearson correlation coefficient, variance analysis and regression study. The study found that there is a good reality for the requirements of applying the marketing quality in the Syrian private commercial banks represented by integrated, internal and social marketing and relationship marketing. هدفت الدراسة إلى تحديد مدى توافر متطلبات تطبيق إدارة الجودة التسويقية في المصارف التجارية الخاصة العاملة في سورية، حيث تكون مجتمع الدراسة من العاملين في هذه المصارف. استخدمت الدراسة المقاربة الاستنباطية كمنهج عام للبحث، والمنهج الوصفي، والاستبانة كأداة لجمع البيانات من عينة ميسرة، حيث تم توزيع (150) استبانة وتم استرداد (135) استبانة صالحة للتحليل. واعتمدت الدراسة أساليب التحليل المناسبة باستخدام الحزمة الاحصائية spss كاختبار ستودنيت ومعامل الارتباط بيرسون وتحليل التباين ودراسة الانحدار. وقد توصلت الدراسة إلى وجود واقع جيد لمتطلبات تطبيق الجودة التسويقية في المصارف التجارية الخاصة السورية والمتمثلة بالتسويق المتكامل والداخلي والاجتماعي والتسويق بالعلاقات.